Nutritional Deficiency - Erkekoglu, Pınar; Kocer-Gumusel, Belma (IntechOpen, 2016)
Intake of a sufficient diet will provide an individual to live a healthy and functional life. However, poor intake of different nutritional components, such as proteins, vitamins, minerals, and trace elements, may lead to health problems that can cause morbidity and finally mortality. Assessment of nutritional status involves physical examination, comprehensive evaluation of biochemical tests, body composition, and organ functions. Both high and low intake of nutritional elements may lead to significant health impairment. The main aim of the book Nutritional Deficiency is to determine the relationships between nutritional status and general health. The authors, who are contributing to the book, particularly focused on iron, vitamin D, and zinc deficiencies, which are global health problems. Besides, some chapters mention the impact of different nutritional deficiencies in susceptible periods of life, such as pregnancy and elderly. Besides, as a result of these deficiencies, different health conditions, such as depression, anemia, loss of neuronal plasticity, and cancer, are widely scrutinized in the book. One chapter mainly focuses on the effects of disasters on nutrition and disaster-caused malnutrition in underdeveloped countries. This book will widen the knowledge store of the readers on the effects of nutrition on general health, how nutritional deficiencies arise when there is a health problem, and how the nutritional status affects susceptible populations.